Study of the Distribution of Normal Contact Pressure Between Parts Joined in a Multi-Bolted System under Operational Loads - Rafał GRZEJDA (Engineering Transactions)
Modelling and calculations of unsymmetrical multi-bolted connections treated as a system for different bolt models and contact layer models between the joined parts are presented. The modelling refers to preloaded and externally loaded connections. The systemic models of the connection for two substitute models of bolts are shown. Between the joined parts two types of the Winkler model of a contact layer are taken into consideration. Calculations were made for an exemplary unsymmetrical connection. Its models were preloaded and externally loaded with normal forces. As a result of the calculations, distributions of normal contact pressure at the interface of the parts joined in the connection are shown.